Industrial training report: Lowyet Centre Muar, Johor / Muhammad Ridhwan Roslan - Roslan, Muhammad Ridhwan (Perpustakaan Tengku Anis, 2017)
The industrial training duration based on the period from 1st August 2017 to 31th December 2017 in Electronic Department Lowyet Centre Muar, Johor. The training consumes 5 months and not more than 6 days of absent. During the industrial training lots of activities being done and lots of new thing being learnt. Most of the main thing learn during industrial training was the software and Hardware because everyday deal with a new problem.For software that need to be learn about how to recover data , backup data , windows recovery , installing software , activate windows also Microsoft office office and setting bios.For hardware that need to be learn about how to service laptop, desktop and troubleshoot a no display or no power board.For developing website PHP programming, wordpress , cpanel that need to be learn for the development of the Lowyet Centre Ecommerce Website. Besides that, need also to learn more about the Hypertext Markup Language (HTML) and Cascading Style Sheet (CSS) that need to be used to redesign template website. The Lowyet Centre Electronic Department really focus on the system development for the organization and also used outside sources for the system development. The staff that work in Lowyet Centre Electronic Department are friendly and well experienced staff ...